Studi Cemaran Logam Berat (Fe, Pb, Cd, Cu dan Zn) dalam Umbi Singkong di Sekitar Area Eks Tempat Pemrosesan Akhir Leuwi Gajah - Arry Febrianto; Buchari (Jurnal Serambi Engineering, 2024)
Heavy metals analysis on cassava around ex Leuwi Gajah Landfill aimed to determine the effects of waste and leachate that contain heavy metals on plants nearby. The analysis was conducted from soil and cassava roots samples. The heavy metals compounds that were determined are Fe, Pb, Cd, Cu, and Zn.Sample destruction was conducted by ash method and then analyzed by Atomic Absorption Spectrophotometry with curve calibration method. We also conducted the water content, ash content, and silica content from the sample by gravimetric method. The analysis results were compared with the control variable by the student t-test method. There is no Cd detected on all cassava samples analysis. On the other hand, Pb concentration detected was exceeded the Indonesia National Standard (SNI) and Foodand Agriculture Organization / World Health Organization (FAO/WHO) permissible limits about heavy metals compounds on food and plants. The student t-test result shows that there is a significant difference in heavy metals content between cassava in landfill and cassava control variables.